Silicon-based composite negative electrode material and preparation method thereof
By using a core-shell structure design on the silicon-based negative electrode material and using a carbon layer and/or a metal oxide layer to cover the silicon core, the problem of volume expansion of the silicon-based material during the embedding/delithation process is solved, and better electrochemical performance and stability are achieved.
Patent Information
- Application Number
- CN202311118725.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
Silicon-based negative electrode materials will face large volume expansion problems during the embedded/deliquefaction process, resulting in structural powdering and instability of the solid electrolyte interface, resulting in irreversible capacity loss.
A silicon-based composite anode material adopting a core-shell structure, the shell includes a carbon layer and/or a metal oxide layer. The stability of the material is improved by coating the carbon and/or metal oxide, reducing the expansion rate, and improving electrical conductivity and ion conductivity.
It effectively alleviates the volume expansion problem of silicon-based materials, improves electrochemical performance, enhances the stability and cycling performance of the material, and meets the demand for electrochemical performance of the negative electrode materials.
Smart Images

Figure CN119542367A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of electrode material preparation, and in particular, to a silicon-based composite negative electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have many advantages such as high energy density, long cycle life, low pollution, and no memory effect. They have become the first choice for the power system of the new energy vehicle industry. At present, the mainstream negative electrode material on the market is still graphite negative electrode material, and its low energy density can hardly meet people's growing energy density requirements for power batteries. As a new type of negative electrode material, silicon-based negative electrode material has the advantages of ultra-high theoretical specific capacity, suitable lithium insertion potential, and low cost. However, in the process of lithium insertion / extraction, silicon-based materials will face the problem of large volume expansion, resulting in the pulverization of their structure and the instability of the solid electrolyte interface, which ultimately causes irreversible capacity loss.
[0003] In order to alleviate the volume expansion of silicon-based materials, the common practice is to coat the silicon-based materials. Currently, the main methods for coating silicon-based materials are solid-phase grinding and sintering or vapor deposition, but the particles of the materials synthesized by these two methods are large and the expansion is relatively serious, making the electrochemical performance of silicon-based negative electrodes in long cycles unable to meet actual needs. Summary of the invention
[0004] In view of this, the present application provides a silicon-based composite negative electrode material, which has a core-shell structure, and the outer shell includes a carbon layer and / or a metal oxide layer. It has small size, low expansion rate, excellent conductivity and ion conductivity, and can solve the problem of volume expansion of existing silicon-based materials during use to a certain extent, while better meeting the requirements of negative electrode materials for electrochemical performance.
[0005] In a first aspect, the present application provides a silicon-based composite negative electrode material, which is a core-shell structure, including a silicon core and a shell coated on the surface of the silicon core, wherein the shell includes a carbon layer and / or a metal oxide layer; the particle size of the silicon-based composite negative electrode material is 1nm-25nm.
[0006] In the implementation manner of the present application, the particle size of the silicon core is 0.1nm-10nm; the thickness of the carbon layer is 1nm-8nm.
[0007] In the implementation manner of the present application, the metal oxide layer includes any one of ferroferric oxide, nickel oxide, cobalt oxide and aluminum oxide; and the thickness of the metal oxide layer is 0.1 nm-5 nm.
[0008] In an embodiment of the present application, the shell includes a carbon layer and a metal oxide layer, and the metal oxide layer is located between the silicon core and the carbon layer.
[0009] In an embodiment of the present application, the mass ratio of silicon to carbon in the silicon-based composite negative electrode material is 1:0.6-4.
[0010] In an embodiment of the present application, the silicon-based composite negative electrode material also includes doping elements doped in the carbon layer and / or the metal oxide layer, and the doping elements include one or more of nitrogen, phosphorus and sulfur; the mass ratio of the doping elements in the silicon-based composite negative electrode material is greater than 0 and less than 5%.
[0011] The second aspect of the present application provides a method for preparing the silicon-based composite negative electrode material provided in the first aspect of the present application, comprising the following steps:
[0012] Adding an organic silicon source into a solvent and performing vacuum ultrasonic mixing to obtain an organic silicon source mixed liquid;
[0013] Adding a surfactant, an organic carbon source and / or a metal salt to the organic silicon source mixed solution, and performing vacuum ultrasonic mixing to obtain a silicon-based mixed solution;
[0014] After subjecting the silicon-based mixed liquid to a thermal reaction, a silicon-based composite negative electrode material precursor is obtained;
[0015] The silicon-based composite negative electrode material precursor is transferred to a heating device, a metal reducing agent is added at the vent, and the silicon-based composite negative electrode material is obtained after sintering.
[0016] In the embodiment of the present application, the temperature of the thermal reaction is 140° C.-250° C., and the time of the thermal reaction is 12 h-36 h.
[0017] In the implementation manner of the present application, the heating rate of the sintering is 3°C / min-8°C / min, the holding temperature of the sintering is 600°C-900°C, and the holding time of the sintering is 1.5h-5h.
[0018] In an embodiment of the present application, the organic silicon source includes one or more of tetrabutyl orthosilicate, tetraethyl orthosilicate, diphenylsilane, 3-aminopropyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltrimethoxysilane and ethyltriethoxysilane.
[0019] In an embodiment of the present application, the solvent includes water and ethanol, and the mass ratio of water to ethanol is 1:0.25-4; or the solvent includes one or more liquid alkanes of n-hexane, n-pentane, n-heptane, cyclohexane and cyclopentane.
[0020] In the embodiment of the present application, the organic carbon source includes one or more of melamine, urea, dopamine, glucose, polyvinyl pyrrolidone, tannic acid, benzene and phenolic organic substances.
[0021] In an embodiment of the present application, the metal salt includes any one of an iron salt, a cobalt salt, a nickel salt and an aluminum salt.
[0022] In an embodiment of the present application, the surfactant includes one or more of sodium dodecyl sulfonate, sodium dodecyl sulfate, ammonium dodecyl sulfate, sodium dodecylbenzene sulfonate, dodecyl phosphate, dodecyl betaine, fatty alcohol, triethanolammonium lauryl sulfate, sodium α-olefin sulfonate, cocoyl methyl taurate amine and cocamidopropyl betaine.
[0023] In an embodiment of the present application, the metal reducing agent includes one or more of magnesium powder, aluminum powder, zinc powder and titanium powder.
[0024] In an embodiment of the present application, the method for preparing the silicon-based composite negative electrode material further comprises adding an element dopant to the organic silicon source mixed solution; the element dopant comprises one or more of a nitrogen dopant, a phosphorus dopant and a sulfur dopant.
[0025] The third aspect of the present application provides a silicon-based composite negative electrode material, which is prepared by the preparation method provided by the second aspect of the present application.
[0026] The fourth aspect of the present application provides a battery negative electrode, including a conductive current collector and a negative electrode active material loaded on the conductive current collector, wherein the negative electrode active material includes the silicon-based composite negative electrode material as described in the first aspect or the silicon-based composite negative electrode material obtained by the preparation method of the silicon-based composite negative electrode material as described in the second aspect of the present application.
[0027] A fifth aspect of the present application provides a battery, comprising a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, wherein the negative electrode comprises the battery negative electrode as described in the third aspect.
[0028] A sixth aspect of the present application provides an electrical device, wherein the electrical device comprises the battery as described in the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A flow chart of a method for preparing a silicon-based composite negative electrode material provided in this application;
[0030] Figure 2 A schematic diagram of the structure of a silicon-based composite negative electrode material provided in one embodiment of the present application;
[0031] Figure 3 A schematic diagram of the structure of a silicon-based composite negative electrode material provided in another embodiment of the present application;
[0032] Figure 4This is a scanning electron microscope (SEM) image of the silicon-based composite negative electrode material provided in Example 1 of the present application.
[0033] Description of Figure Numbers
[0034] 100-silicon-based composite negative electrode material; 101-silicon core; 102-shell; 1021-metal oxide layer; 1022-carbon layer. DETAILED DESCRIPTION
[0035] The present application is further described in detail below in conjunction with preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.
[0036] In the present application, all professional terms have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application.
[0037] During the process of lithium insertion / extraction, silicon-based materials will face the problem of large volume expansion, resulting in the pulverization of their structure and the instability of the solid electrolyte interface, and ultimately causing irreversible capacity loss. In order to alleviate the volume expansion of silicon-based materials, the usual practice is to nano-size or coat the silicon-based materials to reduce the size of the silicon-based materials to alleviate the problem of lithium insertion expansion. However, the existing coating methods are mainly solid-phase grinding and sintering or vapor deposition. These two methods either make it impossible for the silicon material and the material it is coated to be tightly combined, or the morphology and structure of the synthesized material are difficult to control, making the electrochemical performance of the silicon-based negative electrode in long cycles unable to meet actual needs.
[0038] In response to the above problems, the present application provides a silicon-based composite negative electrode material, which is a core-shell structure, including a silicon core and a shell coated on the surface of the silicon core, and the shell includes a carbon layer and / or a metal oxide layer. The present application also improves the stability of the material by coating with carbon and / or metal oxides, which can improve the conductivity of the silicon-based composite material on the one hand, and inhibit the expansion of the material by coating on the other hand. The particle size of the silicon-based composite negative electrode material is 1nm-25nm, and it has small size, low expansion rate, excellent conductivity and ion conductivity, which can solve the problem of volume expansion of existing silicon-based materials during use to a certain extent, and better meet the requirements of negative electrode materials for electrochemical performance.
[0039] See also Figure 1 and Figure 2 The present application provides a silicon-based composite negative electrode material 100, which is a core-shell structure. The silicon-based composite negative electrode material 100 includes a silicon core 101 and a shell 102 coated on the surface of the silicon core 101. The shell 102 includes a carbon layer and / or a metal oxide layer. In some embodiments of the present application, Figure 1As shown, the shell 102 is a single-layer structure, which can be a carbon layer or a metal oxide layer. Figure 2 As shown, the shell 102 is a two-layer structure, including a metal oxide layer 1021 and a carbon layer 1022, and the silicon-based composite negative electrode material 100 includes a silicon core 101 and a metal oxide layer 1021 coated on the surface of the silicon core, and a carbon layer 1022 coated on the surface of the metal oxide layer 1021. On the one hand, the metal oxide layer 1021 has a large theoretical capacity and good stability, which can improve the electrochemical performance of the silicon-based composite negative electrode material 100; on the other hand, the metal oxide layer 1021 is conducive to the subsequent generation of a dense carbon layer 1022 on its surface. The metal oxide layer 1021 is tightly combined with the silicon core 101 and the carbon layer 1022, which improves the problem of interface connection between the silicon core 101 and the carbon layer 1022, thereby improving ion conduction. The application of the silicon-based composite negative electrode material 100 containing these metal oxides in the negative electrode of the battery can better improve the electrochemical performance of the battery.
[0040] In an embodiment of the present application, the particle size of the silicon-based composite negative electrode material is 1nm-25nm. In some embodiments, the particle size of the silicon-based composite negative electrode material can be 1nm, 2nm, 3nm, 4nm, 5nm, 8nm, 10nm, 15nm, 20nm, 25nm. The particle size of the silicon-based composite negative electrode material of the present application is controlled within the range of 1nm-25nm, and the volume expansion problem of the silicon-based composite negative electrode material during the lithium insertion / extraction process is effectively alleviated by reducing the size. The silicon-based composite negative electrode material is applied in a battery, which can effectively improve the cycle performance and service life of the battery.
[0041] In the implementation mode of the present application, the particle size of the silicon core is 0.1nm-10nm; the thickness of the carbon layer is 1nm-8nm. In some implementation modes, the particle size of the silicon core can be 0.1nm, 0.2nm, 0.5nm, 1nm, 2nm, 3nm, 5nm, 7nm, 8nm, 10nm; the thickness of the carbon layer can be 1nm, 2nm, 3nm, 5nm, 6nm, 7nm, 8nm. The silicon core has a high theoretical specific capacity and a suitable lithium insertion potential, but in the process of lithium insertion / extraction, the silicon core will have a large volume expansion phenomenon, which will lead to the pulverization of the battery electrode structure and the instability of the solid electrolyte interface, and never cause irreversible capacity loss of the battery. The present application controls the size of the silicon core of the silicon-based composite negative electrode material within the nanoscale range of 0.1nm-10nm, reduces the size of the silicon-based material, and effectively alleviates the problem of lithium insertion expansion. At the same time, the present application uses a carbon layer and / or a metal oxide layer to coat the silicon core, which also effectively suppresses the volume expansion of the silicon core.
[0042] In an embodiment of the present application, the metal oxide layer includes any one of ferroferric oxide, nickel oxide, cobalt oxide and aluminum oxide. In an embodiment of the present application, the thickness of the metal oxide layer is 0.1nm-2nm. In some embodiments, the thickness of the metal oxide layer can be 0.1nm, 0.2nm, 0.3nm, 0.5nm, 0.6nm, 0.8nm, 1nm, 1.3nm, 1.5nm, 1.8nm, 2.0nm. The metal oxide layer has a large theoretical capacity and good stability, which can improve the stability of the silicon-based composite negative electrode material. In addition, when the shell 102 of the silicon-based composite negative electrode material includes both the metal oxide layer 1021 and the carbon layer 1022, the metal oxide layer 1021 can also improve the problem of the interface connection between the silicon core 101 and the carbon layer 1022, thereby improving ion conduction, so that the silicon-based composite negative electrode material has better electrochemical performance.
[0043] In the embodiment of the present application, when the shell 102 includes a metal oxide layer 1021 and a carbon layer 1022, the silicon-based composite negative electrode material 100 includes a silicon core 101 and a metal oxide layer 1021 coated on the surface of the silicon core and a carbon layer 1022 coated on the surface of the metal oxide layer 1021. On the one hand, the metal oxide layer 1021 has a large theoretical capacity and good stability, which can improve the electrochemical performance of the silicon-based composite negative electrode material 100; on the other hand, the metal oxide layer 1021 is conducive to the subsequent generation of a dense carbon layer 1022 on its surface. The metal oxide layer 1021 is tightly combined with the silicon core 101 and the carbon layer 1022, which improves the problem of interface connection between the silicon core 101 and the carbon layer 1022, thereby improving ion conduction. The application of the silicon-based composite negative electrode material 100 containing these metal oxides in the negative electrode of the battery can better improve the electrochemical performance of the battery.
[0044] In the embodiment of the present application, when the shell 102 includes a carbon layer, the mass ratio of silicon to carbon in the silicon-based composite negative electrode material is 1:0.6-4. In some embodiments, the mass ratio of silicon to carbon in the silicon-based composite negative electrode material can be, for example, 1:0.6, 1:1, 1:1.5, 1:2, 1:3, 1:4. Adjusting the mass ratio of silicon to carbon within a suitable range can enable the prepared silicon-based composite negative electrode material to maintain a smaller nanoscale while having better electrochemical performance and a lower expansion rate.
[0045] In the embodiment of the present application, the silicon-based composite negative electrode material further includes a doping element doped in the carbon layer and / or the metal oxide layer, and the doping element includes one or more of nitrogen, phosphorus and sulfur; the mass ratio of the doping element in the silicon-based composite negative electrode material is greater than 0 and less than 5%. By doping the silicon-based composite negative electrode material with elements such as nitrogen, phosphorus and sulfur, the electronic transmission performance of the material can be improved, so that the negative electrode material obtains better conductivity, thereby improving the electrochemical performance of the battery.
[0046] The silicon-based composite negative electrode material provided by the present application has a small silicon core size, which makes the obtained silicon-based composite negative electrode material small in size, and the expansion rate of the material is significantly reduced by coating with carbon materials and / or metal oxides. In addition, the silicon-based composite negative electrode material can further improve the conductivity and ion conductivity of the material by coating the silicon core with carbon materials and oxides, and can also dope some elements to it. The silicon-based composite negative electrode material is applied to the battery negative electrode to meet the battery negative electrode's requirements for expansion rate and electrochemical performance.
[0047] The present application also provides a method for preparing the silicon-based composite negative electrode material as described above, which uses an organic silicon source to form a silicon core and obtains the silicon-based composite negative electrode material through a solvent thermal reaction. The liquid phase method has the natural advantage of making the reactants tightly combined, and the physical and chemical properties of the product can be regulated by changing the formula of adding substances to the solvent. The preparation method is novel and simple in preparation. The silicon-based composite negative electrode material obtained has a small size and a low expansion rate. In addition, the preparation method can also dope the silicon-based composite material with elements to make it have excellent electrical conductivity and ion conductivity, which solves the problem of volume expansion of silicon-based materials during use and meets the requirements of negative electrode materials for electrochemical performance.
[0048] See also Figure 3 , Figure 3 The flowchart of the method for preparing the silicon-based composite negative electrode material provided in the present application. The method for preparing the silicon-based composite negative electrode material provided in the present application comprises the following steps:
[0049] S101, adding an organic silicon source to a solvent, and performing vacuum ultrasonic mixing to obtain an organic silicon source mixed solution;
[0050] S102, adding a surfactant, an organic carbon source and / or a metal salt to the organic silicon source mixed solution, and performing vacuum ultrasonic mixing to obtain a silicon-based mixed solution;
[0051] S103, subjecting the silicon-based mixed solution to a thermal reaction to obtain a silicon-based composite negative electrode material precursor;
[0052] S104, transferring the silicon-based composite negative electrode material precursor to a heating device, adding a metal reducing agent at the vent, and obtaining a silicon-based composite negative electrode material after sintering.
[0053] The silicon-based composite negative electrode material prepared by the above-mentioned preparation method of the present application is a core-shell structure, including a silicon core and a shell coated on the surface of the silicon core, and the shell includes a carbon layer and / or a metal oxide layer.
[0054] In the embodiment of the present application, the organosilicon source in step S101 includes one or more of tetrabutyl orthosilicate, tetraethyl orthosilicate, diphenylsilane, 3-aminopropyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltrimethoxysilane and ethyltriethoxysilane. The organosilicon source is the raw material for forming the silicon core in the silicon-based composite negative electrode material. The liquid phase method has the natural advantage of making the reactants tightly combined, and the physical and chemical properties of the product can be regulated by changing the formula of adding substances to the solvent. Compared with the commonly used silicon source silicon powder, the dispersion of the organosilicon source in the solvent is more uniform. On the one hand, it is easier to adjust the structure of the silicon-based composite negative electrode material. On the other hand, it can make the prepared silicon core have a smaller particle size, which better alleviates the expansion of lithium insertion.
[0055] In some embodiments of the present application, the solvent in step S101 includes water and ethanol. The mass ratio of water to ethanol is 1:0.25-4. Specifically, in some embodiments, the mass ratio of water to ethanol can be 1:0.25, 1:0.33, 1:0.5, 1:0.66, 1:1, 1:1.5, 1:2, 1:3, 1:4. In some other embodiments of the present application, the solvent in step S101 includes one or more liquid alkanes of n-hexane, n-pentane, n-heptane, cyclohexane, and cyclopentane. The use of the above-mentioned organic solvents in the present application can be more conducive to the uniform dispersion of the organosilicon source.
[0056] In the embodiment of the present application, the surfactant in step S102 includes one or more of sodium dodecyl sulfate, sodium dodecyl sulfate, ammonium dodecyl sulfate, sodium dodecylbenzene sulfonate, dodecyl phosphate, dodecyl betaine, fatty alcohol, triethanolammonium lauryl sulfate, sodium α-olefin sulfonate, cocoyl methyl taurine amine and cocamidopropyl betaine. The addition of surfactant is conducive to the dissolution of organic carbon sources and the like in the organic silicon source mixed solution, plays a role in dispersing the organic silicon source, making the organic silicon source hydrophilic at one end and lipophilic at the other end, isolating and dispersing the synthesized particles, and obtaining a uniformly mixed silicon-based mixed solution, which is conducive to making the final product have a smaller particle size.
[0057] In the embodiment of the present application, the organic carbon source in step S102 includes one or more of melamine, urea, dopamine, glucose, polyvinyl pyrrolidone, tannic acid, benzene, and phenolic organic matter. The organic carbon source is a raw material for forming a carbon layer. The carbon layer obtained by the solvent thermal reaction of the organic carbon source is finally coated on the surface of the silicon core or the metal oxide layer, which can inhibit the expansion of the silicon-based composite negative electrode material and significantly improve the conductivity of the material. Compared with the inorganic carbon source, the organic carbon source is more evenly dispersed in the solvent, which is conducive to the formation of the final small particle size product.
[0058] In the embodiment of the present application, the metal salt in step S102 includes any one of an iron salt, a cobalt salt, a nickel salt and an aluminum salt. In some embodiments, the iron salt may be, for example, ferric chloride, the cobalt salt may be, for example, cobalt nitrate, the nickel salt may be, for example, nickel sulfate, and the aluminum salt may be, for example, aluminum chloride. After the solvothermal reaction, the metal salt becomes an oxide of iron, cobalt, nickel, and aluminum and is coated on the surface of the silicon core to obtain the metal oxide layer 1021 in the silicon-based composite negative electrode material 100 described above. In some embodiments, the metal salt may be ferric dichloride tetrahydrate, and after the solvothermal reaction, a dense iron oxide layer is obtained on the surface of the silicon core. In some embodiments, the metal oxide layer may be formed as an intermediate layer between the silicon core and the outermost carbon layer. In this embodiment, on the one hand, the theoretical capacity of the metal oxide layer is large, the stability is good, and the cost is low; on the other hand, the presence of the metal oxide layer is conducive to the subsequent generation of a dense carbon layer on its surface, which improves the problem of the interface connection between the silicon core and the carbon layer, thereby improving the ion conduction. The application of silicon-based composite negative electrode materials containing these metal oxides in the negative electrode of the battery can better improve the electrochemical performance of the battery.
[0059] In an embodiment of the present application, step S102 also includes adding an elemental dopant to the organic silicon source mixture. In some embodiments, the elemental dopant includes one or more of a nitrogen dopant, a phosphorus dopant, and a sulfur dopant; the elemental dopant can be an organic silicon source and / or an organic carbon source containing a doping element, or can be additionally added. Doping silicon-based composite negative electrode materials with elements such as nitrogen, phosphorus, and sulfur can improve the electron transport properties of the material, so that the negative electrode material obtains better conductivity. In some embodiments, the elemental dopant can be, for example, melamine. On the one hand, melamine can be used as an organic carbon source, and on the other hand, melamine can be used as a nitrogen dopant.
[0060] In the embodiment of the present application, the mixing method in step S101 and step S102 is vacuum ultrasound. The present application uses vacuum ultrasound to mix the organic silicon source mixed liquid and the silicon-based mixed liquid, so that the organic silicon source is dispersed more evenly and the particle size of the final silicon-based composite negative electrode material is smaller.
[0061] In the embodiment of the present application, the thermal reaction of step S103 is a solvent thermal reaction of the material, the temperature of the solvent thermal reaction is 140°C-250°C, and the time of the solvent thermal reaction is 12h-36h. In some embodiments, the temperature of the solvent thermal reaction can be 140°C, 150°C, 160°C, 170°C, 175°C, 180°C, 190°C, 200°C, 220°C, 240°C, 250°C, and the time can be 12h, 14h, 15h, 16h, 18h, 20h, 22h, 24h, 25h, 26h, 28h, 30h, 32h, 34h, 36h. After the solvent thermal reaction is completed, cooling, washing, and drying operations can be performed.
[0062] In the implementation manner of the present application, the heating rate of sintering in step S104 is 3°C / min-8°C / min, the holding temperature is 600°C-900°C, and the holding time is 1.5h-5h. In some specific implementation manners, the heating rate of sintering can be 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, the holding temperature can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, and the holding time can be 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h. The heating equipment can be, for example, a tubular furnace.
[0063] In the embodiment of the present application, the metal reducing agent in step S104 includes one or more of magnesium powder, aluminum powder, zinc powder and titanium powder. The metal reducing agent added during the sintering process can reduce the silicon oxide obtained after the solvent thermal reaction to obtain a silicon-based composite negative electrode material including a silicon core and a carbon layer coated on the surface of the silicon core. The silicon oxide is reduced to obtain nano-scale silicon, so that the obtained silicon-based composite negative electrode material is nano-sized, which effectively reduces the size of the obtained product and alleviates its expansion phenomenon.
[0064] The preparation method of the silicon-based composite negative electrode material provided in the present application uses an organic silicon source instead of the commonly used silicon powder as the raw material of the silicon core in the silicon-based composite negative electrode material. The preparation method is novel and simple, which is conducive to large-scale production and application. In addition, the preparation method is a liquid phase method, and the core and shell of the silicon-based composite negative electrode material with a core-shell structure are tightly combined. Its structure can be easily controlled by changing the components in the solvent, enriching the structure of the negative electrode material. The silicon-based composite negative electrode material prepared by this preparation method is small in size, low in expansion rate, and good in electrochemical performance, which can meet the battery's demand for electrode materials.
[0065] The present application also provides a silicon-based composite negative electrode material, which is prepared by the preparation method described above.
[0066] The present application also provides a battery negative electrode, which includes a conductive current collector and a negative electrode active material loaded on the conductive current collector, and the negative electrode active material includes the silicon-based composite negative electrode material provided above or the silicon-based composite negative electrode material prepared by the preparation method described above.
[0067] The present application also provides a battery, which includes a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, and the negative electrode includes the battery negative electrode provided above.
[0068] The present application also provides an electric device, which includes the battery provided above. The electric device may be, for example, an electric car, a mobile phone, a tablet computer, a laptop computer, a wearable device (a watch, a bracelet), a digital camera, etc.
[0069] The present application is further described below in multiple embodiments:
[0070] Example 1
[0071] 20mL of tetrabutyl orthosilicate was added to a reactor mixed with water and ethanol, with a mass ratio of water to ethanol of 1:1, and the mixture was transferred to a vacuum device for ultrasonication for 0.5h. Then 2g of melamine, 1.5g of ferric chloride tetrahydrate, and 0.2g of sodium dodecyl sulfonate were added to the above reactor, and vacuum ultrasonication was continued for half an hour. The reactor was placed in an oven at 200°C for 24h, then naturally cooled, washed and dried. After drying, the product was transferred to a tubular furnace, and the magnesium metal added at the vent was heated to 600°C at a rate of 3°C / min, kept warm for 3.5h, and sintered to obtain a silicon-based composite negative electrode material-nitrogen-doped Si@Fe3O4@C. Among them, A@B@C is a shell-core structure in which C encapsulates B encapsulates A from the outside to the inside. Figure 4 This is a scanning electron microscope (SEM) image of the silicon-based composite negative electrode material prepared in Example 1.
[0072] Example 2
[0073] Add 20mL of tetrabutyl orthosilicate to a reactor mixed with water and ethanol, with a mass ratio of water to ethanol of 1:1, and transfer the mixture to a vacuum device for ultrasonication for 0.5h. Then add 2g of melamine and 0.2g of sodium dodecyl sulfate to the above reactor, and continue vacuum ultrasonication for half an hour. Put the reactor in an oven at 200℃ for 24h, then cool naturally, wash and dry. After drying, transfer the product to a tubular furnace, add magnesium metal at the vent, heat to 600℃ at a rate of 3℃ / min, keep warm for 3.5h, and obtain a silicon-based composite negative electrode material-nitrogen-doped Si@C after sintering.
[0074] Example 3
[0075] Add 20mL of tetrabutyl orthosilicate to a reactor mixed with water and ethanol, with a mass ratio of water to ethanol of 1:1, and transfer the mixture to a vacuum device for ultrasonication for 0.5h. Then add 1.5g of ferric chloride tetrahydrate and 0.2g of sodium dodecyl sulfate to the above reactor, and continue vacuum ultrasonication for half an hour. Put the reactor in an oven at 200℃ for reaction for 24h, then cool naturally, wash and dry. After drying, transfer the product to a tubular furnace, add magnesium metal at the vent, heat to 600℃ at a rate of 3℃ / min, keep warm for 3.5h, and obtain a silicon-based composite negative electrode material - Si@Fe3O4 after sintering.
[0076] Example 4
[0077] Add 40mL of diphenylsilane to a reactor mixed with water and ethanol, with a mass ratio of water to ethanol of 1:1, and transfer the mixture to a vacuum device for ultrasonication for 0.5h. Then add 2g of melamine, 1.5g of ferric chloride tetrahydrate, and 0.2g of sodium dodecyl sulfonate to the above reactor, and continue vacuum ultrasonication for half an hour. Put the reactor in an oven at 200℃ for reaction for 24h, then cool naturally, wash and dry. After drying, transfer the product to a tubular furnace, add magnesium metal at the vent, heat to 600℃ at a rate of 3℃ / min, keep warm for 3.5h, and obtain a silicon-based composite negative electrode material-nitrogen-doped Si@Fe3O4@C after sintering.
[0078] Example 5
[0079] Add 20mL of tetrabutyl orthosilicate to a reactor mixed with water and ethanol, with a mass ratio of water to ethanol of 1:1, and transfer the mixture to a vacuum device for ultrasonication for 0.5h. Then add 2g of polyvinyl pyrrolidone, 1g of ammonium chloride, 1.5g of ferric chloride tetrahydrate, and 0.2g of sodium dodecyl sulfate to the above reactor, and continue vacuum ultrasonication for half an hour. Put the reactor in an oven at 200℃ for 24h, then cool naturally, wash and dry. After drying, transfer the product to a tubular furnace, add magnesium metal at the vent, heat to 600℃ at a rate of 3℃ / min, keep warm for 3.5h, and obtain the silicon-based composite negative electrode material Si@Fe3O4@C after sintering.
[0080] Example 6
[0081] 20mL of tetrabutyl orthosilicate was added to a reactor mixed with water and ethanol, with a mass ratio of water to ethanol of 1:1, and the mixture was transferred to a vacuum device for ultrasonication for 0.5h. Then 2.5g of dimethyl phosphite, 1.5g of ferric chloride tetrahydrate, and 0.2g of sodium dodecyl sulfonate were added to the above reactor, and vacuum ultrasonication was continued for half an hour. The reactor was placed in an oven at 200°C for 24h, then naturally cooled, washed and dried. After drying, the product was transferred to a tubular furnace, and the magnesium metal added at the vent was heated to 600°C at a rate of 3°C / min, kept warm for 3.5h, and sintered to obtain a silicon-based composite negative electrode material-phosphorus-doped Si@Fe3O4@C. Among them, A@B@C is a shell-core structure in which C encapsulates B encapsulates A from the outside to the inside.
[0082] Comparative Example 1
[0083] Add 20mL of tetrabutyl orthosilicate to a reactor mixed with water and ethanol, with a mass ratio of water to ethanol of 1:1, and transfer the mixture to a vacuum device for ultrasonication for 0.5h. Then add 2g of melamine, 1.5g of ferric chloride tetrahydrate, and 0.2g of sodium dodecyl sulfate to the above reactor, and continue vacuum ultrasonication for half an hour. Put the reactor in an oven at 200°C for reaction for 24h, then cool naturally, wash and dry. After drying, transfer the product to a tubular furnace, heat it to 600°C at a rate of 3°C / min, keep it warm for 3.5h, and sinter to obtain a silicon-based composite negative electrode material-nitrogen-doped SiO x @Fe3O4@C.
[0084] Comparative Example 2
[0085] Add 20mL of tetrabutyl orthosilicate to a reactor mixed with water and ethanol, with a mass ratio of water to ethanol of 1:1, and stir the mixture for 0.5h. Then add 2g of melamine, 1.5g of ferric chloride tetrahydrate, and 0.2g of sodium dodecyl sulfate to the above reactor and continue stirring for half an hour. Put the reactor in an oven at 200°C for 24h, then cool naturally, wash and dry. After drying, transfer the product to a tubular furnace, and heat the magnesium metal added at the vent to 600°C at a rate of 3°C / min, keep warm for 3.5h, and obtain a silicon-based composite negative electrode material-nitrogen-doped SiO after sintering. x @Fe3O4@C.
[0086] Comparative Example 3
[0087] Commercial silicon-carbon anode materials.
[0088] Performance Testing
[0089] The particle size of the silicon-based composite negative electrode material in the embodiment and the comparative example was detected by the laser particle size analyzer method / instrument; the thickness of the shell layer and the diameter of the silicon core in the silicon-based composite negative electrode material prepared in the embodiment and the comparative example were detected by the TEM method / instrument; the carbon content in the silicon-based composite negative electrode material was tested by thermogravimetry; the content distribution of the doping elements in the outer shell layer of the silicon-based composite negative electrode material was tested by EDS, and the results are shown in Table 1.
[0090] Table 1 Performance test results of silicon-based composite negative electrode materials
[0091]
[0092] The silicon-based negative electrode materials prepared in the embodiment and the comparative example were mixed with acetylene black and sodium carboxymethyl cellulose at a mass ratio of 8:1:1 and then coated on copper foil to obtain a negative electrode. A metal lithium sheet was used as a counter electrode, a PE / PP composite diaphragm (polyethylene / polypropylene) was used as an ion exchange membrane, and an electrolyte (including 12.93 parts of LiPF6, 26.95 parts of EC, 30.89 parts of EMC, 11.62 parts of DMC, 10.60 parts of DEC, 5 parts of FEC, and 2 parts of VC by mass) was injected to prepare a button battery, and the performance of the button battery was tested using a blue battery test system.
[0093] The button cell was discharged at 0.5C constant current to 0.005V at 25°C, and then charged to 1.5V at 0.5C constant current. The discharge capacity and charge capacity of the button cell were recorded, and the charge and discharge efficiency (coulomb efficiency) was calculated, where the charge and discharge efficiency (%) = 100% × charge capacity / discharge capacity, and the first coulomb efficiency was obtained. Before assembling the button cell, the initial thickness h0 of each group of negative electrodes was measured with a micrometer. After the button cell was made and cycled 100 times, it was discharged to 0SOC, the button cell was disassembled and the negative electrode sheet was taken out, cleaned with diethylmethylammonium chloride solution, and the thickness h1 of the negative electrode after the cycle was measured after drying, and the expansion rate was calculated, where the expansion rate (%) = 100% × (h1-h0) / h0. The test results are shown in Table 2.
[0094] Table 2 Structural parameter test data of silicon-based composite negative electrode materials prepared in Examples 1-6 and Comparative Examples 1-3
[0095]
[0096]
[0097] It can be seen from the data of Examples 1-6 and Comparative Examples 1-3 in Table 2 that the silicon core particle size of the core-shell structured silicon-based composite negative electrode material provided by the present application is all below 5 nm, which is much smaller than the commercial silicon-carbon negative electrode material in the comparative example, so that the size of the final silicon-based composite negative electrode material is controlled at 25 nm or less. Compared with Comparative Example 1 without reduction treatment and Comparative Example 2 without ultrasonic treatment, the silicon-based composite negative electrode material obtained in Examples 1-6 has a smaller particle size, larger capacity, better cycle performance, and better electrochemical performance. In addition, compared with Comparative Examples 1-3, the expansion rate of the silicon-based composite negative electrode material in Examples 1-6 of the present application is all below 30%, with better cycle performance and longer service life.
[0098] The preferred embodiments are described in detail above, but the present invention is not limited to the above-mentioned specific implementation modes. Under the guidance of the present application, technicians in this field can also make various specific changes without departing from the scope of protection of the present application, which all fall within the scope of protection of the present invention.
Claims
1. A silicon-based composite negative electrode material, characterized in that: The silicon-based composite negative electrode material is a core-shell structure, including a silicon core and a shell coated on the surface of the silicon core, wherein the shell includes a carbon layer and / or a metal oxide layer; the particle size of the silicon-based composite negative electrode material is 1nm-25nm.
2. The silicon-based composite negative electrode material according to claim 1, characterized in that: The particle size of the silicon core is 0.1nm-10nm; the thickness of the carbon layer is 1nm-8nm.
3. The silicon-based composite negative electrode material according to claim 1, characterized in that: The metal oxide layer includes any one of ferroferric oxide, nickel oxide, cobalt oxide and aluminum oxide; and the thickness of the metal oxide layer is 0.1 nm-5 nm.
4. The silicon-based composite negative electrode material according to claim 1, characterized in that: The shell includes a carbon layer and a metal oxide layer, and the metal oxide layer is located between the silicon core and the carbon layer.
5. The silicon-based composite negative electrode material according to claim 1, characterized in that: The mass ratio of silicon element to carbon element in the silicon-based composite negative electrode material is 1:0.6-4.
6. The silicon-based composite negative electrode material according to claim 1, characterized in that: The silicon-based composite negative electrode material further includes doping elements doped in the carbon layer and / or the metal oxide layer, and the doping elements include one or more of nitrogen, phosphorus and sulfur; the mass ratio of the doping elements in the silicon-based composite negative electrode material is greater than 0 and less than 5%.
7. A method for preparing a silicon-based composite negative electrode material, characterized in that: The following steps are involved: Adding an organic silicon source into a solvent and performing vacuum ultrasonic mixing to obtain an organic silicon source mixed liquid; Adding a surfactant, an organic carbon source and / or a metal salt to the organic silicon source mixed solution, and performing vacuum ultrasonic mixing to obtain a silicon-based mixed solution; After subjecting the silicon-based mixed liquid to a thermal reaction, a silicon-based composite negative electrode material precursor is obtained; The silicon-based composite negative electrode material precursor is transferred to a heating device, a metal reducing agent is added at the vent, and the silicon-based composite negative electrode material is obtained after sintering.
8. The method for preparing a silicon-based composite negative electrode material according to claim 7, characterized in that: The temperature of the thermal reaction is 140°C-250°C, and the time of the thermal reaction is 12h-36h; the heating rate of the sintering is 3°C / min-8°C / min, the insulation temperature of the sintering is 600°C-900°C, and the insulation time of the sintering is 1.5h-5h.
9. The method for preparing a silicon-based composite negative electrode material according to claim 8, characterized in that: The organic silicon source includes one or more of tetrabutyl orthosilicate, tetraethyl orthosilicate, diphenylsilane, 3-aminopropyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltrimethoxysilane and ethyltriethoxysilane; the organic carbon source includes one or more of melamine, urea, dopamine, glucose, polyvinylpyrrolidone, tannic acid and benzene and phenolic organic matter; the metal salt includes any one of iron salt, cobalt salt, nickel salt and aluminum salt; the solvent includes water and ethanol, and the water and ethanol The mass ratio of is 1:0.25-4; or the solvent includes one or more liquid alkanes of n-hexane, n-pentane, n-heptane, cyclohexane and cyclopentane; the surfactant includes one or more of sodium dodecyl sulfonate, sodium dodecyl sulfate, ammonium dodecyl sulfate, sodium dodecylbenzene sulfonate, dodecyl phosphate, dodecyl betaine, fatty alcohol, triethanolammonium lauryl sulfate, sodium α-olefin sulfonate, cocoyl methyl taurate amine and cocamidopropyl betaine; the metal reducing agent includes one or more of magnesium powder, aluminum powder, zinc powder and titanium powder.
10. The method for preparing a silicon-based composite negative electrode material according to any one of claims 7 to 9, characterized in that: The method further comprises adding an element dopant into the organic silicon source mixed solution; the element dopant comprises one or more of a nitrogen dopant, a phosphorus dopant and a sulfur dopant.
11. A silicon-based composite negative electrode material, characterized in that: The silicon-based composite negative electrode material is prepared by the method for preparing a silicon-based composite negative electrode material according to any one of claims 7 to 10.
12. A negative electrode of a battery, characterized in that: It comprises a conductive current collector and a negative electrode active material loaded on the conductive current collector, wherein the negative electrode active material comprises the silicon-based composite negative electrode material as described in any one of claims 1 to 6 or the silicon-based composite negative electrode material prepared by the method for preparing the silicon-based composite negative electrode material as described in any one of claims 7 to 10.
13. A battery, characterized in that: The battery comprises a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, and the negative electrode comprises the battery negative electrode as claimed in claim 12.
14. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 13.
Citation Information
Cited By
Low-expansion silicon-carbon negative electrode material and preparation method and application thereof
CN120784340A
A low-expansion silicon-carbon negative electrode material, a preparation method therefor, and an application thereof
CN120784340B
Green low-energy-consumption low-expansion silicon-carbon negative electrode as well as preparation method and application thereof
CN120809792A